INFORMATION SYSTEMS SECURITY IN SPECIAL AND PUBLIC LIBRARIES: AN ASSESSMENT OF STATUS - Ismail, Roesnita; A.N., Zainab (Malaysian Journal of Library and Information Science, 2017)
Explores the use of an assessment instrument based on a model named library information systems security assessment model (LISSAM) to assess the ISS status in special and public libraries in Malaysia. The study aims to determine the implementation status of technological and organizational components of the LISSAM model. An implementation index as well as a scoring tool is presented to assess the IS safeguarding measures in a library. Data used was based on questionnaires distributed to a total of 50 individuals who are responsible for the information systems (IS) or IT in the special and public libraries in Malaysia. Findings revealed that over 95% of libraries have high level of technological implementation but 54% were fair poorly on organizational measures, especially on lack of security procedures, administrative tools and awareness creation activities.